Feminisme Gelombang Kedua Dalam Film “Enola Holmes” - Teguh Dwi Putranto; Francesca Thalia Satiadhi; Arista Amelinda (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Wiraraja, Sumenep, 2022)
Currently, media with the subject of women's rights are emerging, discussing women's issues and sexual orientation such as break-even relations, welfare, and sexual orientation disparities in various divisions. Films are no exception, where the issue of feminism is a genre that is widely discussed, one of which is in the film “Elona Holmes”. This study aims to find out how the second wave of feminism in the film “Elona Holmes” is. John Fiske's semiotics was chosen as a method in this research on the movie